Sholawat Listening Therapy Reduces Anxiety of Preoperative Patients Undergoing General Anesthesia - Devi Ayu Oktavia; Taufan Arif; Rudi Hamarno; Supono (Journal of Ners and Midwifery, 2026)
Anxiety experienced by pre-general anesthesia patients increases respiratory frequency and heart rate, potentially leading to surgery cancellation. This study aims to evaluate the effect of listening to sholawat on anxiety of pre general anesthesia patients at Karsa Husada Hospital Batu, East Java, in March 2024. Quasi-experimental method. Non-Equivalent Group Pre and Post Test design and purposive sampling. The sample consisted of 20 patients divided into control and treatment groups. The independent variable is listening, with anxiety as the dependent variable. Therapy was given before surgery for 5-10 minutes. Data analysis used paired t test and independent t test. The study showed a significant difference between the pre-test and post-test results of the control group (p-value: 0.000). However, the post-test results in the control group showed a non-significant difference (p-value: 0.083). Independent t-test confirmed the effect between the two variables, with the significance value of the post-test of both groups <0.05. Ear stimulation, the pituitary gland and the right brain release endorphins that lower blood levels of stress hormones such as adrenocorticotropic hormone and increase feelings of happiness. It is expected that health workers apply non-pharmacological therapy listening to sholawat to reduce the anxiety of pre general anesthesia patients. Keywords: listening to prayers, anxiety, pre operative general anasthesia.